2021
DOI: 10.1017/s0022149x21000080
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils fromOcimum basilicumcultivars: analysis of their composition and determination of the effect of the major compounds onHaemonchus contortuseggs

Abstract: The continuous use of synthetic anthelmintics against gastrointestinal nematodes (GINs) has resulted in the increased resistance, which is why alternative methods are being sought, such as the use of natural products. Plant essential oils (EOs) have been considered as potential products for the control of GINs. However, the chemical composition and, consequently, the biological activity of EOs vary in different plant cultivars. The aim of this study was to evaluate the anthelmintic activity of EOs from cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The stereochemistry was identified as E based on the coupling constant for the trans protons J H7–H8 =16 Hz (Spekreijse et al. 2012 ; Sitrallah et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The stereochemistry was identified as E based on the coupling constant for the trans protons J H7–H8 =16 Hz (Spekreijse et al. 2012 ; Sitrallah et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“… 2015 ; Sousa et al. 2021 ). In another study, Eugenol and other essential oils of OS have shown anthelminthic activity against the free-living nematode Caenorhabditis elegans (Asha et al.…”
Section: Discussionmentioning
confidence: 99%
“…A previous in vitro study (Sousa et al. 2021 ) on nematode Haemonchus contortus showed the anti-helminthic potential of O. basilicum essential oils. Although the anthelminthic activities of Ocimum species and its essential oils have been studied, nevertheless, the anti-filarial effect of Ocimum sp.…”
Section: Introductionmentioning
confidence: 89%
“…42 An H. contortus egg hatching assay revealed weak activity for 3.12 (IC 50 187 mg mL −1 ) 43 and 3.13 (IC 50 186 mg mL −1 ) 43 and even lower levels of activity for R-carvone (3.15) (IC 50 302 mg mL −1 ), 43 Scarvone (3.16) (IC 50 362 mg mL −1 ) 43 and citral (3.17) (IC 50 353 mg mL; 43 IC 50 300 mg mL −1 ). 44 The monoterpene (3R,6R)-linalool oxide acetate (3.18) isolated from Ajania nubigena (Asteraceae) inhibited motility of the mouse whipworm T. muris (IC 50 20 mg mL −1 ). 45 The sesquiterpene a-santonin (3.19) (C. elegans ED 50 280 mg mL −1 ) 46 rst isolated by Kahler in 1830 from the medicinal Artemisia cina (Asteraceae, "Wormseed") 47,48 has found historic application as an anthelmintic, however, like many early anthelmintics, its use was discontinued aer more potent anthelmintics were developed with reduced side effects.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…42 An H. contortus egg hatching assay revealed weak activity for 3.12 (IC 50 187 μg mL −1 ) 43 and 3.13 (IC 50 186 μg mL −1 ) 43 and even lower levels of activity for R -carvone ( 3.15 ) (IC 50 302 μg mL −1 ), 43 S -carvone ( 3.16 ) (IC 50 362 μg mL −1 ) 43 and citral ( 3.17 ) (IC 50 353 μg mL; 43 IC 50 300 μg mL −1 ). 44…”
Section: Plantsmentioning
confidence: 99%